Kaizen – rozwój japońskiej ewolucyjnej metody zarządzania zmianą - Piasecka-Głuszak, Agnieszka (Kaizen – the development of Japanese evolution method of change management, 2009)
Nowadays in the world economy companies have to deal with problems every day. In order to fulfill customers’ needs they seek for improvements, modify their processes, implement processoriented activity and the way of thinking, i.e. kaizen. The fundamental belief for this approach is that improving all processes every day, both technological and organizational, may lead a company to success in the market, also at international level. This article’s objective is to present Japanese kaizen concept, the history of its development, as well as to introduce its main pillars, such as: 5S practice, proper maintenance of work place; loss recognition and elimination (jp. muda); standardization and visual management
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 371-381